Metabolic detoxification and ace-1 target site mutations associated with acetamiprid resistance in Aedes aegypti L - Samal, Roopa Rani; Panmei, Kungreiliu; Lanbiliu, P.; Kumar, Sarita (Frontiers in Physiology, 2022)
Despite the continuous use of chemical interventions, Aedes-borne diseases remain on the rise. Neonicotinoids are new, safer and relatively effective pharmacological interventions against mosquitoes. Neonicotinoids interact with the postsynaptic nicotinic acetylcholine receptors (nAChRs) of the insect central nervous system but the absence of nAChR polymorphism in resistant phenotypes makes their involvement in neonicotinoid resistance uncertain. Thus, we investigated the role of metabolic detoxification and target site insensitivity in imparting acetamiprid resistance in Ae. aegypti larvae. The studies were conducted on parent susceptible strain (PS), acetamiprid-larval selected strain for 5 generations (ACSF-5; 8.83-fold resistance) and 10 generations (ACSF-10; 19.74-fold resistance) of Ae. aegypti. The larval selection raised α-esterases and β-esterases activity by 1.32-fold and 1.34-fold, respectively in ACSF-10 as compared to PS, while corresponding glutathione-S-transferase and acetylcholinesterase activity increased by 22.5% and 2%. The ace-1 gene in PS and ACSF-10 showed four mismatches in the 1312 – 1511 bp region due to mutations in Y455C codon (Tyrosine to Cysteine) at 1367th position (TACTGC); I457V codon (Isoleucine to Valine) at 1372 bp and 1374 bp (ATAGTG); and in R494M codon (Arginine to Methionine) at 1484 bp (AGGATG). The R494M mutation was the novel and dominant type, observed in 70% ACSF-10 population and hasn’t been reported so far. The studies evidenced the combination of metabolic detoxification and target site mutation in imparting acetamiprid resistance to Ae. aegypti.